The Effectiveness of Stone Column Spacing in Reducing the Potential of Liquefaction - Maulana Arif; Meilani Adriyati (Universitas Negeri Yogyakarta, 2021)
ABSTRACTLiquefaction is a liquefied soil phenomenon caused by cyclic load or earthquake. One of the soil liquefaction prevention methods is the installation of stone column. The stone column is a column filled with compacted rock fragments. It has 50 cm in diameter and 5 m deep This method is believed to reduce the excess pore water pressure that occurs during an earthquake. The stone column has been applied in many construction projects which located in high potential of liquefaction area. This research aims to know the effectiveness of stone column in reducing the liquefaction potential. This research conducted by using borelog data and soil laboratory test. This research also runs the numerical simulation of soil liquefaction with stone column stabilization. The variations in column spacing (2 m; 1.5 m; and 1 m) and subsurface review point (1 m; 1.5 m; 2 m; and 2.5 m) will be applied by using Quake/W from Geostudio 2012 software. The results show that the liquefaction potential can be reduced with the closer stone column spacing up to 1.5 m. Reduction of pore water pressure and liquefaction potential only occurs in the initial period of the earthquake before reaching the peak of earthquake acceleration.ABSTRAKLikuefaksi merupakan fenomena pencairan tanah akibat adanya beban siklik atau gempa. Salah satu metode penanganan likuefaksi yaitu dengan melakukan instalasi stone column. Stone column merupakan suatu kolom yang diisi oleh fragmen batuan yang dipadatkan. Umumya kolom berukuran diameter 50 cm dan kedalaman hingga 5 m. Metode ini dipercaya dapat mengurangi tekanan air pori yang terjadi pada tanah saat gempa. Penelitian ini bertujuan untuk mengetahui efektifitas stone collumn dalam mengurangi potensi likuefaksi. Penelitian ini dilakukan dengan menggunakan data bor dan uji laboratorium. Simulasi numeris juga dilakukan berupa permodelan tanah dengan stabilisasi stone column. Variasi pada jarak stone solumn (2m; 1,5m; dan 1m) dan titik tinjau (1m; 1,5m; 2m; dan 2,5m) dilakukan dengan menggunakan perangkat lunak Quake/w dari Geostudio 2012. Hasil menunjukkan bahwa potensi likuefaksi dapat berkurang dengan jarak stone column yang semakin dekat hingga 1,5 m. Pengurangan tekanan air pori dan potensi likuefaksi hanya terjadi pada periode awal gempa sebelum mencapai puncak percepatan gempa.